FILSAFAT ILMU DALAM PENGEMBANGAN AGAMA ISLAM: Menuju Kualitas Sarjana Muslim - Asrori, Mohammad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
In the Moslem Era people lost their basic of epistemology. Their thought has inflexibly normative and dogmatized. It is just like to understand their doctrine on the real texts. Memorizing and practicing their religious rituals has become only: for doing the formality. They, then, depending on the new science, excavating of the research, and understanding of the Quran and Sunnah context is closely ignored. Moreover, in understanding the essential value of their teaching is inclined a priori apologetic, exclusively lack of interaction and dialogue with the philosophy, such as nowadays’ development on sciences. Because of that, the existence of philosophy can inspire the Muslims academician to be aware of being Muslims humanity by philosophy-methodology-empiricism-rationalism approach as well as to come into being dialogue interaction culture with various approaches of theology, sociology, empiricism, history, anthropology, positivism, etc. Those have been grown in this world, hence, it can turn up many academicians as scientists around us.